Ultra-long-acting (XLA) antivirals for chronic viral hepatitis. (January 2022) - Soriano, Vicente; Alvarez, Carmen; Edagwa, Benson; de Mendoza, Carmen; Montoya, Noemí; Treviño, Ana; Gendelman, Howard
ABSTRACT: Viral hepatitis is among the top four causes of mortality globally, causing 1.4 million deaths each year, exceeding tuberculosis, malaria and human immunodeficiency virus. Hepatitis B and C are responsible for 90% of hepatitis deaths, and the remaining 10% are caused by other hepatitis viruses. The annual number of deaths from hepatitis C is declining, whereas the numbers of deaths from hepatitis B and D are increasing. Hepatitis B alone represents the seven highest cause of mortality worldwide. Spurred on by development of curative antivirals for hepatitis C and expanding access to hepatitis B virus (HBV) vaccination, the World Health Organization has committed to eliminating viral hepatitis as a public health threat by 2030. Like the majority of current antivirals, those available for HBV are virostatic. They are capable of suppressing viral replication but cannot eliminate the virus from infected patients. Therefore, treatment is lifelong. Long-term adherence to medication continues to represent a major challenge. Importantly, HBV often reactivates, leading to potential life-threatening events in immunosuppressed patients. Therapeutic options are limited for hepatitis D; however, promising new, effective antivirals are on the horizon. Recent advances have emerged in medicinal chemistry and drug delivery approaches to produce ultra-long-acting (XLA) antivirals. These can extend antiviral activity from months to 1 year or even longer. These new formulations can overcome the challenges of daily dosing and maximize drug exposure. The development of XLA antivirals targeting viral hepatitis may also facilitate cure strategies.